2016
DOI: 10.3389/fpsyt.2016.00199
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive Processes in Anorexia Nervosa in the Time Course of Cognitive-Behavioral Therapy: A Pilot Study

Abstract: ObjectivePrevious studies report reduced interoceptive abilities in anorexia nervosa (AN) using various methods. Recent research suggests that different levels of interoceptive processes aiming at different subdomains of interoceptive abilities must be further distinguished as these levels can be differentially affected. Two important levels refer to interoceptive accuracy (IA) derived from objective performance tasks such as the heartbeat detection task and interoceptive sensibility (IS) as assessed by self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 56 publications
4
43
3
Order By: Relevance
“…In contrast to previous reports (Fischer et al, ; Pollatos et al, ), but in line with others (Ambrosecchia et al, ; Eshkevari et al, ), we did not find evidence for lower heartbeat perception in AN patients compared with HCs using a heartbeat perception task. This may be due to sample differences (e.g., inpatient vs. outpatient, smaller sample sizes, or presence of comorbidities) and resulting heterogeneity in weight and treatment progress.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In contrast to previous reports (Fischer et al, ; Pollatos et al, ), but in line with others (Ambrosecchia et al, ; Eshkevari et al, ), we did not find evidence for lower heartbeat perception in AN patients compared with HCs using a heartbeat perception task. This may be due to sample differences (e.g., inpatient vs. outpatient, smaller sample sizes, or presence of comorbidities) and resulting heterogeneity in weight and treatment progress.…”
Section: Discussionsupporting
confidence: 71%
“…This may be due to sample differences (e.g., inpatient vs. outpatient, smaller sample sizes, or presence of comorbidities) and resulting heterogeneity in weight and treatment progress. Whereas we tested 37 AN patients (~80% of restrictive type) at different stages of treatment, Fischer et al () tested 15 AN patients with a restrictive type at three relatively systematic measurement points. Furthermore, Pollatos et al () recruited 28 AN outpatients (~80% of restrictive type), suggesting that treatment progress may be of importance when investigating interoceptive deficits in AN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of the nonsignificant mediation effect concerning the cortisol/DHEA ratio, future studies should also use larger sample sizes to increase statistical power for the mediation analyses. In addition to this, an investigation of patients with somatic or mental disorders would be interesting due to reported IAcc impairments in such populations (Dunn, Dalgleish, Ogilvie, & Lawrence, 2007;Fischer et al, 2016;Pollatos & Georgiou, 2016;Schultchen et al, 2019;Weiss et al, 2014). In this regard, Weiss and colleagues found that individuals with somatic disorders show decreased IAcc and self-regulation.…”
Section: Future Researchmentioning
confidence: 99%